Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Untuk Meningkatkan Keaktifan Peserta Didik Kelas 1 Sekolah Dasar - Muhammad Kurnia Ghani; Wahyu Hastini; Dedi Pramono (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
The purpose of this research is to increase the activeness of students in the learning process in the classroom. This study uses Kemmis and Mc. Taggart model of classroom action research (CAR). This research model consists of stages of planning, implementation, and observation, as well as reflection. The subjects of this study were the first-grade students of SD Negeri Balirejo, totaling 19 students. Data collection techniques using observation and documentation techniques. Descriptive data analysis technique using percentages. Based on the results of the study, it was concluded that the application of the student team achievement division learning model could increase the activity of grade 1 students at SD Negeri Balirejo. In the pre-cycle, the percentage obtained was 62.50% with the